2018
DOI: 10.1016/j.cllc.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Clinical Outcomes Among Metastatic Non–Small-Cell Lung Cancer Patients Treated in the Community Practice Setting

Abstract: Targeted therapy and immunotherapy was most frequently used in the 2L and 3L setting during the study time frame. Survival differences observed according to treatment types are likely because of biologic differences, and suggest that patients with actionable mutations have a survival advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 15 publications
5
57
1
Order By: Relevance
“…Therefore, the treatment patterns observed in the current study reflect the US FDA approval future science group www.futuremedicine.com erlotinib received from 2004 onwards as monotherapy for the treatment of patients with metastatic NSCLC, regardless of genetic mutation status, after failure of at least one prior chemotherapy regimen. The median OS observed in this study (11.1 months from metastatic NSCLC diagnosis and 10.1 months from the start of first-line therapy) was generally consistent with reports in the literature [8,29]. We observed a significant survival benefit with first-line immunotherapy monotherapy compared with first-line chemotherapy/nonimmunotherapy combination therapy and monotherapy (median OS: 17.5 vs 15 months and 6.8 months, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the treatment patterns observed in the current study reflect the US FDA approval future science group www.futuremedicine.com erlotinib received from 2004 onwards as monotherapy for the treatment of patients with metastatic NSCLC, regardless of genetic mutation status, after failure of at least one prior chemotherapy regimen. The median OS observed in this study (11.1 months from metastatic NSCLC diagnosis and 10.1 months from the start of first-line therapy) was generally consistent with reports in the literature [8,29]. We observed a significant survival benefit with first-line immunotherapy monotherapy compared with first-line chemotherapy/nonimmunotherapy combination therapy and monotherapy (median OS: 17.5 vs 15 months and 6.8 months, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…More than one quarter (26.7%) of patients had no recorded systemic treatments, and the median OS from diagnosis was <1 year. Most patients received first-line platinum-based chemotherapy consistent with both clinical guidelines and other real-world studies conducted during a similar time period [6][7][8]29]. Notably, the current study observed treatment patterns related to the approval and uptake of immunotherapy into clinical practice from 2015 onwards; in the second line of treatment, we observed that nivolumab was initiated after first-line platinum-based chemotherapy in nearly a third of patients.…”
Section: Discussionsupporting
confidence: 81%
“…These results are similar to those observed in the study conducted by Nadler et al [16], in which 71% of the observed population was initially treated with platinum-based chemotherapy, and to those observed in other smaller published real-world utilization studies of similar time frames reporting ranges from 61 to 85% utilization of platinum-based chemotherapy as first line-treatment [17,18]. However, within the scenario of second-line treatment, the use of docetaxel in our study was much higher than that observed in the aforementioned studies, being used in 47% of our patients versus the observed range of 14-16% [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…EGFR mutation was tested in 73.9% of our population and was positive in 36.5% of these patients; ALK translocation was tested in 11.3% and was positive in 15.4%. In the study by Nadler et al [16] in the USA, EGFR and ALK status was available in approximately 40% and 35% of the patients, respectively. Among those with documented results, EGFR and ALK status was positive in 13% and 3% of the patients, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, even in current study, Pemetrexed (30.3%, 22.7%) and Cisplatinum (23.9%, 13.6%) were the most frequently used chemotherapeutic drugs as 1st and 2nd line, respectively whereas, among TKIs, Ge tinib (31.5%, 17.4%) and Icotinib (20.3%, 15.9%) were the frequently used treatment in 1st and 2nd line, respectively. This treatment pattern is not in line with other patterns reported elsewhere wherein docetaxel was used in 14.0-16.0% of patients in 2nd line (25,26).…”
Section: Discussioncontrasting
confidence: 82%